INCREASING E-BANKING AWARENESS TO BRI KCP DIPONEGORO CUSTOMERS THROUGH BRIMO USE OF SOCIALIZATION - Arya Putra Sanjaya, I Ketut Gede; Oktavia Gama, Adie Wahyudi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The development of information technology is very influential in the business world, and it is very fast as it is felt today, making the business world develop rapidly because the two are interconnected and need each other. One of the companies that develops information technology is Banking. Banking develops information technology by creating an application called Electronic Banking or E-Banking. To increase BRImo users to make it easier for customers to open accounts and make transactions, BRI provides socialization to its customers to use BRImo. The benefits of this service activity for students are that they can apply the theory obtained in higher education with real practice in the world of work and society, for universities, namely to expand the introduction of majors, and for companies, namely providing input and considerations to further improve the quality and quantity of the company. The purpose of this service is to find out the factors that influence the use of BRImo in BRI KCP Diponegoro customers. The method used in this service activity is to always provide education and socialization about the benefits obtained if you use the BRImo application.